Beyond oneself: the ethics and psychology of awe. Issue 1 (9th June 2020) - Paulson, Steve; Sideris, Lisa; Stellar, Jennifer; Valdesolo, Piercarlo
Abstract: Awe and wonder appear to be powerful emotions that can inform and shape our attitudes toward ourselves and others, especially in relation to the larger meaning and purpose of our lives. What are the psychological underpinnings of these universal emotions? How does awe, for example, relate to self‐knowledge, and more generally to understanding the enigmatic contradictions of human nature? Is it possible to cultivate and develop this emotion as an ethical incentive in our relationships with others? Are awe and wonder capable of awakening and engendering moral transformation? Does the emotion of awe lie at the root of the religious impulse in humans? and Is there any room left for a sense of the miraculous in today's increasingly scientific and secular world? Professor of religious studies Lisa Sideris joins psychologists Jennifer Stellar and Piercarlo Valdesolo to explore how awe shapes our perspectives and views on everything from science to morality.